تصوّر تنظیمِ وقت : مغربی اور اسلامی تناظر کا ایک مطالعہThe Concept of Time Management: A Study of the Western and Islamic Perspectives (Al-Qamar, 2022)
It is a well-established myth that most of the existing concept of time management is developed by Western Scholars. But if we read Quran, Seerah and Islamic history carefully we can easily understand that time management is well taught in Islamic teachings. Time is a precious commodity and amana of Allah (swt). Well managed utilization of time leads to success in this worldly life and the life hereafter. So we must utilize it mindfully in the best possible manner. The purpose of this paper is to prove in the light of authentic sources that: the concept of “Time management is life management” is in fact an Islamic concept; that Islam presents the best guidelines on time management in all aspects of life and all roles of a person and that Islam presents the best system to identify time wasters and how to avoid them. So we do not need to borrow time management techniques from west.
Keywords: Time management; Islamic and Western concepts